Production of wine from the fruit pulp of African star apple (Chrysophyllum albidum G.Don,) (2014)
African star apple Chrysophyllum albidum G.Don, (Sapotaceae) is an important forest tree species and valued for its fruits among forest dwellers across West and Central Africa. Utilization efficiency of the fruit pulp in Nigeria is limited to consumption as fruit snack during its season. Hence there are a lot of wastages offruits which are not marketed within few days of harvesting. Processing of the fruit pulp for industrial development may promote better utilization efficiency and sustainable management of the species. The study therefore investigated the potentials of the fruit pulp of the species in wine production. Fruits used for the study were collected from old and young trees at Laniba, Akinyele Local Government Area, Ibadan, Nigeria. Ripe fruits were plucked from young and old trees and the juice extracted from the fruit pulp. The wine was prepared by fermenting the juice, using graded levels of sucrose to produce dry and sweet wines. Chemical, microbial, heavy metals and sensory properties of the wine were determined. Heavy metals concentrations were within the WHO limits. Young and old trees fruit wines contain: Cr (22.74ppm/mg, 20.46ppm/mg), Pb (8.4ppm/mg, 2.4ppm/mg) and Mn (10.8ppm/mg, 9.6ppm/mg) respectively. The ascorbic acid contents were higher in old tree and sweet wine samples than young tree and dry wine samples (3.28 and 3.59%) and (2.06 and 2.11%) respectively. African star apple has good potentials as a raw material for fruit wine production. Food industries may consider the adoption of this indigenous species for fruit wine production